2016
DOI: 10.1016/j.lungcan.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in pleural mesothelioma: A review of the 13th International Conference of the International Mesothelioma Interest Group

Abstract: Imaging plays an important role in the detection, diagnosis, staging, response assessment, and surveillance of malignant pleural mesothelioma. The etiology, biology, and growth pattern of mesothelioma present unique challenges for each modality used to capture various aspects of this disease. Clinical implementation of imaging techniques and information derived from images continue to evolve based on active research in this field worldwide. This paper summarizes the imaging-based research presented orally at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The IASLC/IMIG Mesothelioma Registry found that histology, age, sex, and white blood cell and platelet counts stratified survival for 906 patients; further validation can be found in the eighth edition of the Mesothelioma Staging Registry . Greater emphasis on preoperative quantitation imaging studies, including CT volume of the pleural mesothelioma or linear measurements at 3 levels or of diaphragm thickness, also may add to clinical/laboratory stratification. In the immediate future, greater use of novel IHC, genomic, and immune‐based tissue biomarkers may influence whether surgical therapy is indicated.…”
Section: Staging and Prognosismentioning
confidence: 99%
“…The IASLC/IMIG Mesothelioma Registry found that histology, age, sex, and white blood cell and platelet counts stratified survival for 906 patients; further validation can be found in the eighth edition of the Mesothelioma Staging Registry . Greater emphasis on preoperative quantitation imaging studies, including CT volume of the pleural mesothelioma or linear measurements at 3 levels or of diaphragm thickness, also may add to clinical/laboratory stratification. In the immediate future, greater use of novel IHC, genomic, and immune‐based tissue biomarkers may influence whether surgical therapy is indicated.…”
Section: Staging and Prognosismentioning
confidence: 99%
“…Moreover, direct, histological assessment of the mediastinum should be considered, particularly in light of emerging data regarding the prognostic importance of mediastinal nodal involvement in MPM (see 'Staging'). Importantly, MRI also allows more precise estimation of pleural tumour volume [16] and acquisition of functional data [17] that may be useful in future T-staging and early detection strategies. Local Anaesthetic Thoracoscopy (LAT) images recorded in the same patient demonstrating widespread parietal pleural tumour (some highlighted by white arrows) after complete evacuation of the large pleural effusion.…”
Section: The Key Investigations: Chest Radiography Ultrasound and Comentioning
confidence: 99%
“…Therapeutic options appear likely to increase in the near future. MRI may also prove to be a better screening tool than CT, since it does not involve exposure to ionising radiation and offers superior precision [16] and complementary (but as yet unproven) diagnostic functional end-points [17]. In addition, recent data suggests that reconstruction of cumulative life-time asbestos exposure and accurate modelling of lifetime MPM risk is possible [109], and may better select individuals most likely to benefit.…”
Section: Early Detectionmentioning
confidence: 99%
“…For screening of an at-risk population, only less invasive methods like imaging can be employed. Unfortunately, imaging methods for MM screening are currently not available 9 , 10 . The non-circular tumor growth pattern of MM and the differentiation of pleural changes, especially between early MM and plaques, is challenging when interpreting computed tomography (CT) scans 11 .…”
Section: Introductionmentioning
confidence: 99%